A Modified Version Of The Geomechanics Classification For Entry Design In Underground Coal Mines - David A. Newman (Society for Mining, Metallurgy & Exploration, 1985)
The Geomechanics Classification (Bieniawski, 1979) was modified for entry and roof support design in underground room-and-pillar coal mines. Adjustment multipliers were introduced to incorporate the influence of strata weatherability, high horizontal stresses, and the roof support reinforcement factor into the existing classification system. Sixty-two case histories of both standing and fallen mine roof were collected from two mines in the northern Appalachian coalfield. Twenty-seven engineering and geologic parameters were recorded for each case. A partial correlation analysis was carried out on the cases to establish which parameters have a significant impact upon the supported stand-up time of coal mine roof. Survival analysis, a statistical technique used in medical research to assess the effect of a drug or treatment on a patient's life expectancy, was conducted together with stepwise multiple regression to derive values for the adjustment multipliers. A practical example is included to illustrate the application of the modified Geomechanics Classification to underground coal mine design.